(3bUjOI GdQMehfjs - (3GdQMehfj, eMeO GdUGdM Hf SdjeGf Hf eMeO, J(B1242(3g`s
(3ChdgG (B:s
(3Cbhd bhdG eGdG jbGd dbGFdg efGOjG Ydg jUZj ajeJKds
(3BNQgG (B:s
(3efc CRci UdGI OGFeI eG OGe fLe GdSeGA HGddjd jTJYds
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe(B: 6 / 163s
(3eYLe GdeDdajf(B: 3 / 353s
(3eUOQ GbJfGA GdCUd (B:s
(3OGQ GdcJH GdbWQjIs
(3ehGUaGJ GdhYGA (B:s
Keywords: (3GdJUha hGdBOGH GdTQYjIs